War Powers : How the Imperal Presidency Hijacked the Constitution - Irons, Peter (New York Metropolitan Books, 2005)
This book examines a fundamental question in the development of the American empire: What constraints does the Constitution place on our territorial expansion, military intervention, occupation of foreign countries, and on the power the president may exercise over American foreign policy? Worried about the dangers of unchecked executive power, the Founding Fathers deliberately assigned Congress the sole authority to make war. But the last time Congress declared war was on December 8, 1941, after the Japanese attack on Pearl Harbor. Since then, every president from Harry Truman to George W. Bush has used military force in pursuit of imperial objectives, while Congress and the Supreme Court have virtually abdicated their responsibilities to check presidential power. Legal historian Irons recounts this story of subversion from above, tracing presidents' increasing willingness to ignore congressional authority and even suspend civil liberties. -- From publisher description.
Include Conclusion, Notes, Suggested Reading and Sources and Index
Keywords: War and emergency powers -- United States -- History